2020
DOI: 10.1021/acsomega.0c00338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen on Hg0 Adsorption on Non-Impregnated Activated Carbons

Abstract: Both physisorptive and chemisorptive mechanisms play a role in the adsorption of mercury. The present publication investigates the influence of oxygen on the adsorption of Hg 0 by breakthrough curve measurements and temperature-programmed desorption (TPD) experiments. The presence of O 2 in the gas phase promotes chemisorption. Because of slow adsorption mechanisms, no equilibrium capacities of mercury chemisorption can be determined. For further investigations, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…Since more mercury is chemisorptively bound to the activated carbons at low temperatures, this effect seems to dominate over the deceleration of the reaction kinetics by lowering the rate constant. In contrast, Ambrosy et al 37 found faster kinetics with increasing temperature in the case of chemisorption of Hg 0 with oxygen. This can be understood by assuming that the required activation energy for the chemisorption of mercury with water is lower than for the chemisorption of mercury with oxygen.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Since more mercury is chemisorptively bound to the activated carbons at low temperatures, this effect seems to dominate over the deceleration of the reaction kinetics by lowering the rate constant. In contrast, Ambrosy et al 37 found faster kinetics with increasing temperature in the case of chemisorption of Hg 0 with oxygen. This can be understood by assuming that the required activation energy for the chemisorption of mercury with water is lower than for the chemisorption of mercury with oxygen.…”
Section: Resultsmentioning
confidence: 87%
“…In the energy balance of the fluid phase G, the energy exchange between the fluid and solid phases, the transport terms of convection and dispersion, the storage terms of the gas phase, and the heat transport through the adsorber wall are considered. 30,37…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature shows that both physisorptive and chemisorptive interactions play a role in the adsorption of mercury on activated carbons. In previous publications, we have already reported in detail on the current state of literature on simulative and experimental investigations of the adsorption of Hg 0 . …”
Section: Introductionmentioning
confidence: 99%
“…For a complete separation of elemental mercury, Hg 0 -impregnated activated carbons with high capacity are used, which bind mercury by chemisorption. However, the kinetics of chemisorptive deposition are very slow. As a result, a rapid breakthrough of mercury is observed, especially when cleaning discontinuous waste gas streams with pronounced concentration peaks. For such applications the concept of a multilayer adsorber might be suitable.…”
Section: Introductionmentioning
confidence: 99%